2022
DOI: 10.1007/s00330-022-09217-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of fibrosis in hypertrophic cardiomyopathy: a radiomic study on cardiac magnetic resonance cine imaging

Abstract: Objectives Hypertrophic cardiomyopathy (HCM) often requires repeated enhanced cardiac magnetic resonance (CMR) imaging to detect fibrosis. We aimed to develop a practical model based on cine imaging to help identify patients with high risk of fibrosis and screen out patients without fibrosis to avoid unnecessary injection of contrast. Methods A total of 273 patients with HCM were divided into training and test sets at a ratio of 7:3. Logistic regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…55 Radiomics and AI have also been widely applied for the task of differentiating various cardiomyopathies, with the main focus lying on the different etiologies of the hypertrophic heart including (but not limited to) hypertrophic cardiomyopathy based on LGE or cine imaging, or, more recently, mapping. [56][57][58] Several studies also investigated the usefulness of radiomics to detect the presence or extent of myocardial fibrosis without relying on gadolinium contrast, either using native T1-weighted imaging, 59 cine imaging, 60 or T1/T2 mapping. 61 Radiomics and T1 mapping were also utilized to differentiate different hypertrophic cardiomyopathy genotypes and phenotypes 62,63 and to predict outcomes in patients with hypertrophic cardiomyopathy.…”
Section: Clinical Applications Of Radiomics and Ai In Cardiac Imaging...mentioning
confidence: 99%
“…55 Radiomics and AI have also been widely applied for the task of differentiating various cardiomyopathies, with the main focus lying on the different etiologies of the hypertrophic heart including (but not limited to) hypertrophic cardiomyopathy based on LGE or cine imaging, or, more recently, mapping. [56][57][58] Several studies also investigated the usefulness of radiomics to detect the presence or extent of myocardial fibrosis without relying on gadolinium contrast, either using native T1-weighted imaging, 59 cine imaging, 60 or T1/T2 mapping. 61 Radiomics and T1 mapping were also utilized to differentiate different hypertrophic cardiomyopathy genotypes and phenotypes 62,63 and to predict outcomes in patients with hypertrophic cardiomyopathy.…”
Section: Clinical Applications Of Radiomics and Ai In Cardiac Imaging...mentioning
confidence: 99%
“…Recognizing the potential of radiomics in extracting comprehensive information for images, research focusing on radiomics based on CMR cine sequences is on the rise. Limited studies have indicated that radiomics based on CMR cine sequences can effectively identify myocardial fibrosis and scar [ 15 19 ]. Furthermore, it has demonstrated the capability to differentiate myocardial amyloidosis from hypertrophic cardiomyopathy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a last example, Pu et al reported that a radiomics-based predictive model was able to identify myocardial fibrosis in patients with hypertrophic cardiomyopathy with high diagnostic accuracy, using cine images only. 9 Such an approach exhibits clinical potential by providing fibrosis assessment without the need for contrast administration. While it would be difficult to discuss every cardiac MRI related radiomics study considering the limits of an editorial, it can be generally concluded that most, if not all, of the prior studies focused on features of the cardiac chambers (i.e.…”
mentioning
confidence: 99%
“…They demonstrated high accuracy in the discrimination of patients with hypertrophic and dilated cardiomyopathies from each other and from healthy participants. As a last example, Pu et al reported that a radiomics‐based predictive model was able to identify myocardial fibrosis in patients with hypertrophic cardiomyopathy with high diagnostic accuracy, using cine images only 9 . Such an approach exhibits clinical potential by providing fibrosis assessment without the need for contrast administration.…”
mentioning
confidence: 99%